Shear Bond Strength of Self-Adhesive Flowable Resin Composite - Norah Sibai; Aminah El Mourad; Nohair Al Suhaibani; Raghad Al Ahmadi; Sara Al Dosary (Hindawi Limited, 2022)
This study aimed to evaluate the shear bond strength of self-adhesive flowable resin composite on both enamel and dentin and investigate whether surface pretreatment with a phosphoric acid etch affects the bond strength. In this in vitro study, 80 sound human premolars were flattened to create (40) uniform enamel (E) and (40) dentin (D) surfaces. Groups were divided according to surface pretreatment: E1 : Scotchbond™ Universal Etchant + Single Bond Universal Adhesive + Filtek™ Z350 XT flowable composite; E2: Single Bond Universal self-etch adhesive + Filtek Z350 XT flowable composite; E3 : Scotchbond Universal Etchant + Fusio Liquid Dentin self-adhesive flowable composite; E4: Fusio Liquid Dentin self-adhesive flowable composite; D1 : Scotchbond Universal Etchant + Single Bond Universal Adhesive + Filtek Z350 XT flowable composite; D2: Single Bond Universal self-etch adhesive + Filtek Z350 XT flowable composite; D3: Scotchbond Universal Etchant + Fusio Liquid Dentin self-adhesive flowable composite; D4: Fusio Liquid Dentin self-adhesive flowable composite. After 2500 thermal cycles, the SBS was measured with a universal testing machine. One-way analysis of variance and Tukey's test for multiple comparisons were used to compare results. Two-way ANOVA was done to observe the significance of interaction between the type of surface and treatment. The maximum (49.38 ± 1.23 MPa) and minimum (21.41 ± 5.27 MPa) SBS values were noted in groups D1 and E2, respectively. Shear bond test results showed that self-adhesive flowable composite exhibited similar shear bond strengths on enamel and dentin and the bond strength improved with selective acid etching.